Exploring Legal Protections for E-Commerce Businesses in the Risks of Cash on Delivery Transactions - Alfian, Rifki (Universitas Pendidikan Nasional, 2024)
This research examines the legal protection for e-commerce businesses in Indonesia in Cash-on-delivery (COD) transactions that are vulnerable to the risk of consumers' cancellation or refusal of payment. Although the COD method provides security and convenience for consumers, it can cause business losses to businesses when the delivered goods are rejected or not paid for by consumers. The research uses a normative juridical approach by analyzing the Consumer Protection Law No. 8 of 1999 and other relevant regulations related to e-commerce in Indonesia. Based on the analysis, results show that legal protection for business actors in Indonesia's face of payment rejection is still inadequate, which creates additional risks for producers in the form of logistics costs and decreased quality of goods. The study recommends increasing the role of e-commerce platforms as fair mediators, setting firmer consumer obligations related to responsibility in transactions, and educating consumers about the economic impact of payment refusal, with these steps expected to create balanced protection for consumers and businesses and support the sustainable growth of e-commerce in Indonesia.